Green Macroalgae Biomass Upcycling as a Sustainable Resource for Value-Added Applications - Ana Terra de Medeiros Felipe; Alliny Samara Lopes de Lima; Emanuelle Maria de Oliveira Paiva; Roberto Bruno Lucena da Cunha; Addison Ribeiro de Almeida; Francisco Ayrton Senna Domingos Pinheiro; Leandro De Santis Ferreira; Marcia Regina da Silva Pedrini; Katia Nicolau Matsui; Roberta Targino Hoskin (Applied Sciences)
As the global demand for eco-friendly food ingredients grows, marine macroalgae emerge as a valuable resource for multiple applications using a circular bioeconomy approach. In this study, green macroalgae Ulva flexuosa, naturally accumulated in aquaculture ponds as a residual biomass (by-product) of shrimp and oyster farming, were investigated regarding their bioactivity, chemical composition, and antioxidant properties. The use of aquaculture by-products as raw materials not only reduces waste accumulation but also makes better use of natural resources and adds value to underutilized biomass, contributing to sustainable production systems. For this, a comprehensive approach including the evaluation of its composition and environmentally friendly extraction of bioactive compounds was conducted and discussed. Green macroalgae exhibited high fiber (37.63% dry weight, DW) and mineral (30.45% DW) contents. Among the identified compounds, palmitic acid and linoleic acid (ω-6) were identified in the highest concentrations. Pigment analysis revealed a high concentration of chlorophylls (73.95 mg/g) and carotenoids (17.75 mg/g). To evaluate the bioactivity of Ulva flexuosa, ultrasound-assisted solid–liquid extraction was performed using water, ethanol, and methanol. Methanolic extracts showed the highest flavonoid content (59.33 mg QE/100 g), while aqueous extracts had the highest total phenolic content (41.50 mg GAE/100 g). Ethanolic and methanolic extracts had the most potent DPPH scavenging activity, whereas aqueous and ethanolic extracts performed best at the ABTS assay. Overall, we show the upcycling of Ulva flexuosa, an underexplored aquaculture by-product, as a sustainable and sensible strategy for multiple value-added applications.